Planning of energy carriers based on final energy consumption using dynamic programming and particle swarm optimization - Dehghani, M.; Montazeri, Z.; Ehsanifar, A.; Seifi, A.R.; Ebadi, M.J.; Grechko, O.M. (Електротехніка і електромеханіка, 2018)
Purpose. In the present article, a new approach of the energy grid studies is introduced to program energy carriers. In this view, a proper plan is designed on the use of energy carriers considering the energy optimum use. Indeed, the proper energy grid is designed by applying Iran energy balance sheet information. It is proper to mention that, the energy grid modelling is done in a matrix form. The electrical energy distribution among power stations is achieved by using the particle swarm optimization algorithm. In the present paper, concerning the dynamic programming method, it is tried to determine a suitable combination of energy carriers.